Respuesta :

Answer:

(3,2)

Step-by-step explanation:

2x-4=y

2y+3x=13

We substitute the y in. They already gave us the equation 2x-4=y simplified so you would just plug this into the other equation

2(2x-4) +3x=13 : *distribute*

4x-8+3x=13 :  *combine like terms*

7x-8=13  * add the 8 to the other side*

7x=21 *divide*

x=3

So  the y=2x-4 is what we added in the place of the y to subtract it and solve for x. The second step would be solving for y. So now that we have our answer, 3  we plug it into the other equation preferably.

2(3)-4 =y : 6-4=y : 2=y

We can check our answer by pugging both x and y into both equations to make sure they are right. The statement should be true.

2x-4=y         2(3)-4=(2)    2=2

2y+3x=13    2(2)+3(3)=13    13=13